Promoting the Development of Teacher Professional Knowledge: Integrating Content, Pedagogy and Technology while Teaching - Sridevi, K. V. (Voices of Teachers and Teacher Educators, 2019)
With the changing role of the teacher from a transmitter to a facilitator and advancement of technology in educational discourse, technological knowledge has become an integral part of teacher education programmes. Technology was introduced as an aid to teachers to support their instruction so that teachers can satisfy the diverse learning needs of today’s inclusive classrooms. But acquisition of technological knowledge exclusively as a separate domain during pre-service or inservice teacher education fails to develop understanding of the applications of technology in integration with other basic knowledge domains of teachers’ i.e. content knowledge and pedagogy knowledge. The current paper discusses knowledge structures of teachers and their integration to make science learning more meaningful and interesting. This paper presents the findings of a need based training programme conducted to study knowledge structure of teachers and its integration in the teaching-learning process. 27 in-service secondary school science teachers from 14 states of India participated in the study. Based on the identified needs, knowledge structures were strengthened providing scope for discussions, reflections along with hands on activities during the training. Pre-tests and post-tests were administered to find their knowledge base and confidence levels before and after training to see any improvement in their knowledge structures on integration of content, pedagogy and technology while teaching. Analysis reveals that there is a significant improvement in content knowledge, pedagogical knowledge, technological knowledge and integration of all these among the teachers. Further it was also found that there is a shift in the confidence level from moderately confident to extremely confident and reduction in number of individuals who are not confident when compared before and after training in the content, pedagogical, technological knowledge and their integration.